A general financial transaction tax. Motives, revenues, feasibility and effects - Österreichisches Institut für Wirtschaftsforschung, Vienna; Schulmeister, Stephan; Schratzenstaller, Margit; Picek, Oliver (Vienna, 2008)
"Speculative trading, especially in the financial derivatives markets, not only increases the volatility of exchange rates, prices for raw materials and share prices over the short run but also over the long run, driving these prices away from their "fundamental" equilibriums: long-term upward or downward trends are the result of an accumulation of very short-term price "runs". A general financial transaction tax (FTT) would make short-term transactions in the derivatives markets more expensive and thus help stabilise exchange rates, raw material prices and share prices. The study estimates the revenues to be obtained from a general FTT for European countries, major regions and on a global scale. For Austria, a tax rate of 0.1 percent should yield 0.62 percent of GDP; a tax rate of 0.01 percent would produce 0.21 percent of GDP. In Germany, revenues from tax rates of 0.1 percent, 0.05 percent and 0.01 percent would be 1.50 percent, 1.07 percent and 0.47 percent of GDP, respectively. For the global eonomy in total, a tax rate of 0.1 percent or 0.01 percent would produce 1.52 percent or 0.49 percent of the global GDP. In Europe and North America, a general FTT would yield approximately the same amount (between 2.2 percent and 0.7 percent of GDP)."